Polyurethane composition having improved force retention and moisture resistance

JP2024514198A5Pending Publication Date: 2025-04-21BAY MATERIALS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023563194
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-19
Filing Date
2022-04-19
Publication Date
2025-04-21

AI Technical Summary

Technical Problem

Existing polyurethane compositions lack high yield elongation, high elongation at break, high optical clarity, good stain resistance, and excellent stress retention in the presence of water at moderate temperatures.

Method used

A thermoplastic polyurethane (TPU) reaction mixture comprising a diol component with a general formula HO-(CH 2 ) x -OH, where x is an integer from 9 to 18, and one or more cyclic diols with 6 or more carbons, along with a diisocyanate component including MDI, TDI, PDI, HDI, H12MDI, IPDI, XDI, or CHDI, and a molar ratio of isocyanate groups to alcohol groups (NCO) of 0.95 to 1.05, containing less than 20% polymeric diol with a glass transition temperature below 0°C.

Benefits of technology

The TPU compositions exhibit improved mechanical and optical properties with low water absorption, excellent stress retention, and high glass transition temperatures, suitable for applications requiring thermoformability and resistance to moisture, such as orthodontic aligners.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Improved thermoplastic polyurethane compositions are provided which exhibit a combination of moderate modulus, high elongation at yield, high elongation at break, high optical clarity, good color resistance, good elastic recovery, and excellent stress retention in the presence of water at moderate temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [Related Applications]

[0001] This application claims priority to and claims the benefit of U.S. Provisional Patent Application No. 63 / 176,439, filed April 19, 2021, and entitled "POLYURETHANE COMPOSITIONS HAVING IMPROVED FORCE RETENTION AND MOISTURE RESISTANCE," the entire contents of which are incorporated by reference.

[0002] [Technical field]

[0002] This disclosure relates to improved thermoplastic polyurethane compositions useful for producing medical devices that exhibit a combination of moderate elastic modulus, high yield elongation, high break elongation, high optical clarity, good color resistance, good elastic recovery, and excellent stress retention in the presence of water at moderate temperatures.

[0003] [background]

[0003] There is a large literature on polyurethane chemistry, properties, and preparation, including numerous patents, published patent applications, and books, including Szycher's Handbook of Polyurethanes, Michael Szycher (ed.) CRC Press, July 2012, and Polyurethane Handbook, Gunter Oertel (ed.) Hanser Pub Inc., January 1994. The compositions disclosed herein differ in numerous ways from prior art polyurethanes, as detailed herein below.

[0004]

[0004] U.S. Pat. No. 4,376,835 odiscloses polyurethanes having high modulus and high heat distortion temperature prepared by polymerization of 2-25% polyol having a glass transition temperature below C and a molecular weight of 500-20,000 Daltons, and one or more low molecular weight chain extenders, preferably butanediol, hexanediol, neopentyl glycol, and cyclohexanedimethanol (CHDM). In contrast, the polyurethane compositions described herein are not prepared by polymerization of a polyol and a low molecular weight chain extender.

[0005]

[0005] US Patent No. 4,822,2827 discloses polyurethanes comprising a polyisocyanate component and a polyol component comprising a mixture of one or more cycloalkylenediols or biscycloalkanediols and at least one other chain extender having 2 to 10 carbon atoms. The material may additionally comprise up to 25% of a polymeric polyol having a molecular weight greater than 500. The described materials have a high flexural modulus (greater than about 260,000 PSI), a glass transition temperature of at least 125°C, are relatively brittle, and have an elongation at break of less than about 35%. These materials are reported to be useful in applications requiring resistance to high temperatures. In contrast, the polyurethane compositions described herein are not prepared using a combination of a polyisocyanate component, a polymeric polyol, and a cycloalkylenediol or biscycloalkanediol chain extender having a Tg greater than 125°C.

[0006]

[0006] US Patent Application Publication No. 20180127535 discloses a two-phase polyurethane elastomer with a Shore D hardness of greater than 50, which is composed of a soft block based on about 26-40% polycaprolactone, and a hard block composed of polyisocyanate, and a long-chain diol chain extender. The chain extender may be a linear aliphatic diol having 9-16 carbons. Due to the biphasic nature of the material, the composition has a haze value of approximately 30. The thermoplastic polyurethane (TPU) composition disclosed herein has a haze value of less than 20 and does not contain a soft block with 26-40% polycaprolactone.

[0007]

[0007] WO 2014 / 210099 (US Patent Publication No. 20160122462) discloses a two-phase polyurethane elastomer with a Shore D hardness of less than 60 and good resilience properties, which is composed of about 23-55% polycaprolactone-based soft block, and a hard block composed of polyisocyanate, and a long-chain diol chain extender. The chain extender may be a linear aliphatic diol with 9-16 carbons. Due to the biphasic nature of the material, the composition has a haze value of approximately 30. The TPU composition disclosed herein has a haze value of less than 20 and does not contain a soft block with 26-40% polycaprolactone.

[0008]

[0008] US Patent Application Publication No. 2016311964A1 discloses highly elastic polyurethanes prepared from polyether polyols, linear aliphatic diisocyanates, and linear chain extenders having a crystalline melting point less than 180 C. The TPU compositions disclosed herein are substantially amorphous and exhibit little or no crystallinity.

[0009]

[0009] US Patent Application Publication No. 20180319925A1 discloses a high modulus polyurethane composed of 5-25 wt% polyol, aromatic diisocyanate, and linear diol. 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,3-butanediol, 1,5-pentanediol, 1,9-nonanediol, 1,12-dodecanediol, ethylene glycol, 1,4-benzenedimethylolbenzene glycol, and 1,4-cyclohexanedimethanol are described as useful chain extenders, and the thermoplastic polyurethane may be crystalline when the chain extender is a linear glycol that is unbranched and unsubstituted having 2-12 carbon atoms, for example about 2-9 carbon atoms. The disclosed TPU composition comprises a polyisocyanate component, a diisocyanate having the general structure HO-(CH2) n -OH, where n is equal to 9 to 18; and at least a second cyclic diol having 6 or more carbon atoms, and is prepared by the reaction of a diol component consisting of 5 to 25 weight percent polyol or chain extender.

[0010]

[0010] WO 2020 / 225651 discloses polyurethanes useful for orthodontic applications prepared by reacting a hydrogenated dimer fatty acid (diol) having 36 carbon atoms with a diisocyanate such as MDI and a short chain diol such as hexanediol to produce a polyurethane having hard and soft domains. The hydrogenated dimer fatty acid (diol) having 36 carbon atoms and the short chain diol such as hexanediol are not included in the polyurethane reaction mixture disclosed herein.

[0011]

[0011] US Patent Application Publication No. 2012 / 0329883 A1 discloses water-swellable polyurethanes prepared by polymerizing polyethylene glycol and / or polypropylene glycol with a diisocyanate and a chain extender to produce a multiphase thermoplastic material. Hexanediol, decanediol, and dodecanediol are said to be the preferred chain extenders. The samples tested have high water absorption, with water absorption rates ranging from more than 2% up to 40%. In contrast, the disclosed polyurethane compositions have low equilibrium water absorption.

[0012]

[0012] US Patent Application Publication No. 2015 / 0368392A1 discloses Shore A TPUs prepared from dimer acid based diols (soft block materials) combined with a diol chain extender mixture of linear C12 diols and branched diols, with the branched diols being 15-30% of the total diols. The material is claimed to be clear and hydrophobic, but the use of higher amounts of branched diols resulted in undesirable sticky materials. Neither the dimer acid based diols (soft block materials) nor the branched diol chain extenders are included in the polyurethane reaction mixtures disclosed herein.

[0013]

[0013] There remains a need for TPU compositions that exhibit high elongation at yield, high elongation at break, high optical clarity, good color resistance, and excellent stress retention in the presence of water at moderate temperatures. The present disclosure addresses this need.

[0014] [overview] The present disclosure provides a thermoplastic polyurethane (TPU) reaction mixture comprising a diol component and a diisocyanate component, the diol component having the general formula HO-(CH2) xA TPU reaction mixture is provided that includes at least one linear aliphatic diol having an --OH group, where x is an integer from 9 to 18, and one or more cyclic diols having 6 or more carbons. The molar ratio of isocyanate groups to alcohol groups (NCO ratio) is about 0.95 to 1.05, and the reaction mixture includes less than 20% of a polymeric diol component having a glass transition temperature less than 0° C.

[0015]

[0015] The diisocyanate component of the TPU reaction mixture can include one or more of MDI, TDI, PDI, HDI, H12MDI, IPDI, XDI, CHDI, or HXDI, and the diisocyanate component of the TPU reaction mixture may include greater than 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 88% MDI or H12MDI.

[0016] The diol component of the TPU reaction mixture may contain greater than 80 mole percent cyclohexanedimethanol, 4,4'-isopropylidenedicyclohexanol, and a linear or branched diol having 9 or more carbon atoms.

[0017] The TPU reaction mixture may include an aliphatic diol component including one or more of 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, and dimer alcohols.

[0018] The TPU reaction mixture may include a cyclic diol component including one or more of cyclohexanedimethanol, tetramethylcyclobutanediol, hydrogenated bisphenol A, cyclohexanediol, and isosorbide.

[0019]

[0019] The TPU reaction mixture may include an aromatic diol component comprising one or more of 1,2-benzenedimethanol, 1,3-benzenedimethanol, 1,4-benzenedimethanol, 1,4-bis(2-hydroxyisopropyl)benzene, 1,4-bis(2-hydroxyethyl)benzene, 2,2'-(o-phenylenedioxy)diethanol, resorcinol bis(2-hydroxyethyl)ether, hydroquinone bis(2-hydroxyethyl)ether, and bis(2-hydroxyethyl)terephthalate.

[0020] The present disclosure further provides a TPU composition prepared using the reaction mixture described herein, wherein the TPU (polymer) has the following characteristics: (a) is substantially amorphous and has a glass transition temperature greater than 85° C.; (b) is substantially amorphous and has a glass transition temperature greater than 100° C. or greater than 110° C.; (c) has a stress retention greater than 500 grams or greater than 750 grams; (d) has a water absorption less than 1.80% after 48 hours at 60° C.; (e) has an elongation at yield greater than 7% or 8%; (f) has an elongation at break greater than 55% or greater than 75%; (g) has a dB stain value less than 10 or less than 3. (h) having a flexural modulus of from 500 MPa to 2,500 MPa; (i) having a haze value of less than 10 or less than 6; or (j) a higher TG and substantially no increase in water absorption as compared to thermoplastic polyurethane compositions comprising an aliphatic diol and lacking a cyclic diol.

[0021]

[0021] The present disclosure further provides a TPU composition prepared using the reaction mixture described herein, wherein the TPU (polymer) when thermoformed exhibits a force retention of greater than 800 g when a 0.76 mm thick sample is tested at 5% strain for 24 hours at 37°C.

[0022] The present disclosure further provides polymer sheet compositions and laminates comprising the TPU compositions as disclosed herein.

[0023] Further provided is a reversibly deformable dental appliance conforming to one or more teeth comprising the polymer sheet composition or laminate disclosed herein. [Brief description of the drawings]

[0024] [Figure 1] 1 is a graphical depiction of the relationship between water absorption and shape recovery for an exemplary TPU composition. [Diagram 2] 1 is a graphical depiction of shape recovery as a function of glass transition temperature for exemplary TPU compositions. [Diagram 3] 1 is a graphical depiction of force retention as a function of water absorption for an exemplary TPU composition.

[0025] [Detailed Description]

[0027] Various preferred features and embodiments are described below by way of non-limiting example.

[0026]

[0028] Polyurethanes are used in numerous applications including the production of films, sheets, tubing, molded parts, and coatings. Polyurethane hardness may range from very soft, e.g., less than Shore A35, to stiff, e.g., Shore D85 or higher. Polyurethanes may be used alone or as blends or alloys, and may be combined with fillers or additives, including, for example, flame retardants, glass fibers, waxes, or processing aids. Polyurethanes may be used as a laminate of discreet layers, or as part of a multi-layer structure formed by sequential extrusion or coextrusion.

[0027]

[0029] For example, when used in medical applications to produce dental or orthodontic appliances, polyurethanes should be biocompatible, resistant to staining from materials such as coffee, wine, and mustard, and have low compression set and / or stress relaxation, especially when exposed to body temperature and bodily fluids such as saliva, mucus, or blood. Excellent optical properties, including high light transmission and low haze, are desirable. In some applications, such as dental aligners, the material should have good chemical resistance, especially resistance to stress cracking, and good abrasion resistance. Ideally, the material will not be degraded by alcohol, surfactants, dental care products, or mildly acidic or basic compositions, including lipids found in fingerprints or olive oil, for example.

[0028]

[0030] Polyurethanes may be crosslinked thermosets or thermoplastics and may be processed, for example, by casting, extrusion, molding, thermoforming, or 3D printing. Polyurethanes are typically produced by the reaction of one or more polyisocyanates and one or more diols and / or polyols, which produce repeating urethane groups. Polyurethanes may contain hard and soft microdomains, which are chemically bonded together by urethane bonds. By combining hard and soft regions, some TPUs provide improved strength and toughness while maintaining flexibility. Other polyurethanes may be composed of essentially all hard blocks with a glass transition or melting point above room temperature, for example, above 60°C to about 240°C. Although these materials are not considered elastomers, they may contain small amounts of soft blocks derived from polyols, polyamines, or polythiols to improve certain properties.

[0029]

[0031] Some polyurethanes may additionally contain amide or urea linkages resulting from reaction with amines or water and are called polyurethaneureas.

[0030]

[0032] Due to its desirable properties and excellent biocompatibility, polyurethane is the material of choice for producing dental appliances, including but not limited to aligners, retainers, bite guards, splits, and sports mouth guards. Polyurethane can be formed into appliances by any known method, including thermoforming, molding, 3D printing, or casting, and may be the entire material or part of a layered structure composed of two or more materials.

[0031]

[0033] The technology described herein provides TPU compositions having excellent mechanical and optical properties with improved color resistance, low water absorption, and improved stress retention, and can be prepared by conventional processes using specific polyisocyanates and diols in a one-step (batch) or multi-step process. These polyurethanes are made up of (a) a polyisocyanate component, (b) a diol having the general structure HO-(CH2) x and (c) a diol component comprised of at least a long chain diol having an --OH group, where x is equal to 9 to 18; and at least a second cyclic diol having 6 or more carbon atoms; and optionally a minor polyol component having a molecular weight of 650 to 5,000.

[0032]

[0034] The resulting polyurethanes are substantially amorphous, have glass transition temperatures above about 85° C., and exhibit a favorable combination of mechanical, optical, and thermal properties believed to enhance force retention in the presence of water, and have exceptionally low moisture absorption rates that facilitate drying and thermoforming. The disclosed polyurethanes have particular utility in the production of orthodontic aligners where low stress relaxation in the presence of water at moderate temperatures combined with ease of thermoforming, stain resistance, and excellent clarity are required.

[0033] (definition)

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although other methods and materials similar or equivalent to those described herein can be used in the practice of this disclosure, the preferred materials and methods are described herein. Other features and advantages of the present disclosure will be apparent from the following detailed description and from the claims.

[0034]

[0036] The term "aliphatic diol" is used herein to refer to an organic compound in which carbon atoms are joined by single, double, or triple bonds to form a non-aromatic structure that may be linear, branched, or cyclic and may contain two hydroxyl (OH) groups.

[0035]

[0037] The term "ASTM D638" is used herein to refer to the test for plastic tensile strength. This test is used to evaluate the yield elongation, break elongation, tensile modulus, and Poisson's ratio. Unless otherwise specified, samples were tested using a Type IV tensile bar at a speed of 1.27 cm / min.

[0036]

[0038] The term "ASTM D1364" is used herein to refer to the test for interlayer peel strength.

[0037]

[0039] The term "branched aliphatic diol" is used herein to refer to diols having one or more branches in the carbon chain, for example, neopentyl glycol and 2-butyl-2-ethylpropane diol.

[0038]

[0040] As used herein, the term "compression set" refers to the permanent deformation of a material when a force is applied and removed. Unless otherwise specified, compression set is measured according to ASTM D395-B at a specific time and temperature, e.g., 22 hours at 23°C.

[0039]

[0041] The term "comprises" and its grammatical equivalents are used herein to mean that other features are optionally present in addition to the features specifically identified. For example, a composition or device "comprising" (or "which comprises") components A, B, and C can contain components A, B, and C, or can contain components A, B, and C but also one or more other components.

[0040]

[0042] The term "consisting essentially of" and its grammatical equivalents are used herein to mean that in addition to the features specifically identified, other features may be present which do not materially alter the claimed composition.

[0041]

[0043] The term "at least" followed by a number is used herein to denote the beginning of a range beginning with that number (which may be an upper or lower bound, depending on the variable being defined).

[0042]

[0044] The term "at most" followed by a number is used herein to refer to the end of a range ending at that number (which may be a range with 1 or 0 as its lower limit, or a range with no lower limit, depending on the variable being defined). When a range is given as "from (first number) to (second number)" or "from (first number) to (second number)", this means that the range has a lower limit with the first number and an upper limit with the second number.

[0043]

[0045] The term "cyclic diol" is used herein to refer to a diol having a ring structure, for example, 1,4-cyclohexanedimethanol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, or isosorbide. A cyclic diol may contain one or more ring structures.

[0044]

[0046] The term "stained dB value" or "dB value" refers to the staining of a sample with mustard, as detailed below.

[0045]

[0047] The term "initial color in dB" refers to the color of a sample measured before staining as detailed below.

[0046]

[0048] As used herein with respect to the present disclosure, the term "dimer alcohol" refers to a diol derived from the hydrogenation of a dimer acid, typically having 36 carbon atoms.

[0047]

[0049] As used herein, the terms "dynamic mechanical analysis" and "DMA" refer to tests used to evaluate the thermal and mechanical properties of materials, including loss and storage moduli. As described in more detail below, DMA tests are performed on equipment capable of applying cyclic stress or strain to a material and measuring its response to specific conditions.

[0048]

[0050] As used herein, the term "elongation at break" refers to the percentage increase in length that a material achieves before breaking. Unless otherwise specified, the test method employed herein is ASTM D638.

[0049]

[0051] As used herein, the terms "yield elongation" and "yield elongation" refer to the ability of a plastic sample to withstand a change in shape before irreversibly deforming. Yield elongation is the ratio of the increased length to the initial length at the yield point. The test method employed herein is ASTM D638.

[0050]

[0052] As used herein, the terms "embodiment," "one embodiment," and "some embodiments" refer to specific features, structures, or characteristics described in connection with the present disclosure. Thus, the use of the terms "in one embodiment," "in an embodiment," or "in some embodiments" in various places throughout this specification does not necessarily refer to the same embodiment. Certain features of the present disclosure that are described in the context of separate embodiments may also be provided in combination in a single embodiment. Conversely, features of the present disclosure that are described in the context of a single embodiment may also be provided separately or in one or more subcombinations.

[0051]

[0053] As used herein, the term "dental appliance" refers to any appliance intended to be placed in a subject's mouth or on the teeth, including, but not limited to, orthodontic, prosthetic, retaining, snoring / airway, cosmetic, therapeutic, protective (e.g., mouth guards), and habit-modification devices.

[0052]

[0054] The terms "equilibrium moisture sorption", "water absorption", and "moisture absorption" are used interchangeably herein to refer to the weight percent of water absorption by a sample that is first dried at 100° C. in a vacuum oven for at least 8 hours and then placed in 60° C. water for 48 hours.

[0053]

[0055] As used herein, the term "flexural modulus" refers to the stiffness of a material and / or its resistance to deformation in bending. The higher the flexural modulus of a material, the more resistant the material is to bending. Unless otherwise noted, flexural modulus is measured according to ASTM D790 and is reported as megapascals (MPa) or pounds (force) per square inch (psi).

[0054]

[0056] As used herein, the term "glass transition temperature" refers to the gradual and reversible transition in amorphous and semi-crystalline materials from a "glassy" state to a viscous or rubbery state as temperature is increased, as described in more detail below.

[0055]

[0057] As used herein, the term "hardness" refers to the Shore hardness scale and is measured according to ASTM D2240 unless otherwise stated. Durometer measures the penetration of a metal foot or pin into the surface of a material. There are various durometer scales, but Shore A and Shore D are commonly used. Materials with higher durometer values ​​are harder compared to materials with lower durometer values. Shore hardness and elastic modulus are generally correlated, and if only one value is known, they can be converted by approximation by methods described in the art.

[0056]

[0058] As used herein, the terms "haze" and "haze value" refer to transparency as measured by ASTM D1003, as further detailed below.

[0057]

[0059] As used herein, the terms "elastic modulus," "Young's modulus," and "elastic modulus" refer to the stiffness of a material and / or its resistance to stretching. The higher the elastic modulus of a material, the stiffer it is. The flexural modulus and elastic modulus of a material may be the same or different. For isotropic materials, the flexural modulus and elastic modulus (sometimes called elastic modulus) are substantially the same, and one or the other may be measured depending on the circumstances. For polymers, mechanical properties, including elastic modulus and other properties, may be measured as specified by ASTM D638. Unless otherwise indicated, "elastic modulus" refers to the modulus of elasticity. For isotropic materials, the modulus measured in any direction is the same. For non-isotropic materials, such as laminates, the tensile modulus and flexural modulus may be measured and reported independently.

[0058]

[0060] As used herein, the terms "plurality," "multiple," "plurality," and "multiple" refer to two or more features.

[0059]

[0061] The term "polymeric diol" is used herein to refer to a polymeric material having two alcohol functional groups per molecule, such as polyethylene glycol.

[0060]

[0062] The term "polyol" is used herein to refer to a polymeric material having two or more alcohol groups per molecule, such as polytetramethylene glycol or derivatives having an average of two or more alcohol functional groups per molecule.

[0061]

[0063] As used herein, the term "polymer sheet" is used interchangeably with the term "plastic sheet."

[0062]

[0064] As used herein, the term "shape recovery" refers to the ability of a polymer to recover its shape after 24 hours in deionized water at 37°C at 5% strain. The shape recovery test is used to measure the percentage of the original polymer shape recovered after 24 hours in DI water at 37°C under 5% strain. A polymer strip with dimensions of 101.75 x 25.4 x 0.76 mm (L, w, t) is wrapped around a PVC pipe (diameter 48.25 mm), clamped at two ends, and immersed in DI water at 37°C for 24 hours. At the end of the test period, the clamps are removed and the strip is allowed to recover freely in air for 24 hours. The 24-hour shape recovery (%) is calculated according to the following formula: 24 hour shape recovery (%)=100×(1-(((L-L24) / (L-L0))) [In the formula, L = total length of strip, 101.75mm L0 = distance between the ends of the clamped strip, 43.5 mm L24 = distance between the ends of the free strip after 24 hours of recovery (mm)] is determined in accordance with

[0063]

[0065] As used herein, the terms "force retention" and "stress retention" refer to the force (pound force (lbf), gram force (gf), etc.) required to maintain a particular constant strain.

[0064]

[0066] As used herein, the term "thermoplastic polymer" refers to a polymer that becomes flexible or moldable above a certain temperature and solidifies upon cooling, provided that heat and pressure do not chemically degrade the polymer.

[0065]

[0067] This specification incorporates by reference all documents mentioned herein, including but not limited to those published together with this specification, and all documents filed simultaneously with this specification or previously filed in connection with this application.The TPU composition disclosed herein is prepared by reacting a mixture of two or more components.Also, the reference to the reaction mixture for producing polyurethane composition may be used to refer to the polymer derived from the reaction mixture.

[0066] (Polymer component)

[0068] Polyisocyanate component. The TPU compositions described herein may be produced using one or more polyisocyanates. In some embodiments, the polyisocyanate component comprises one or more of an aromatic diisocyanate, such as phenylene diisocyanate, an aliphatic diisocyanate, a cycloaliphatic diisocyanate, and combinations thereof.

[0067]

[0069] In some embodiments, the polyisocyanate component of the reaction mixture comprises one or more aromatic diisocyanates, including, but not limited to, 4,4'-methylenebis(phenylisocyanate) (MDI), m-xylylene diisocyanate (XDI), phenylene-1,4-diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate (TODI), 1,5-naphthalene diisocyanate (NDI), and toluene diisocyanate (TDI), and modifications of any of the foregoing.

[0068]

[0070] In some embodiments, the TPU composition is prepared using a polyisocyanate component that includes MDI.

[0069]

[0071] In some embodiments, the polyisocyanate component of the reaction mixture includes one or more aliphatic diisocyanates, such as isophorone diisocyanate (IPDI), 1,4-cyclohexane diisocyanate (CHDI), 1,3-bis(isocyanatomethyl)cyclohexane (HXDI), decane-1,10-diisocyanate, lysine diisocyanate (LDI), 1,4-butane diisocyanate (BDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane-4,4'-diisocyanate (H12MDI).

[0070]

[0072] In some embodiments, the TPU composition is prepared using a polyisocyanate component that includes H12MDI.

[0071]

[0073] In some embodiments, the polyisocyanate component is essentially free, or even completely free, of aliphatic diisocyanates.

[0072]

[0074] In some embodiments, the polyisocyanate component is essentially free, or even completely free, of aromatic diisocyanates.

[0073]

[0075] In some embodiments, the polyisocyanate component includes one or more cycloaliphatic isocyanates.

[0074]

[0076] In some embodiments, the reaction mixtures described herein may contain small amounts (less than 5% by weight) of polyester diols derived from caprolactone monomers.

[0075] (Diol component)

[0077] In some embodiments, the diol component of the reaction mixture has the general formula HO-(CH) x The diols include at least one linear aliphatic diol having an --OH group, where x is an integer from 9 to 36, 9 to 30, 9 to 24, or 9 to 18. Examples include 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,14-dodecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, diols derived from polyalphaolefins and hydrogenated butadiene polyols, and combinations thereof.

[0076]

[0078] In some embodiments, the diol component includes at least one branched aliphatic diol, such as 2-butyl-2-ethyl-1,3-propanediol, or neopentyl glycol.

[0077]

[0079] In some embodiments, the diol component of the reaction mixture comprises at least one aromatic diol having a benzene or other aromatic ring, such as 1,2-benzenedimethanol, 1,3-benzenedimethanol, 1,4-benzenedimethanol, 1,4-bis(2-hydroxyisopropyl)benzene, 1,4-bis(2-hydroxyethyl)benzene, 2,2'-(o-phenylenedioxy)diethanol, resorcinol bis(2-hydroxyethyl)ether, hydroquinone bis(2-hydroxyethyl)ether, and bis(2-hydroxyethyl)terephthalate.

[0078]

[0080] In some embodiments, the diol component of the reaction mixture is one or more cyclic diols having six or more carbon atoms, such as cycloaliphatic diols, or diols containing one or more of oxygen, nitrogen, sulfur, or phosphorus atoms, such as 1,3 or 1,4-cyclohexanedimethanol (CHDM), 1,2,1,4, or 1,3-cyclohexanediol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCBD), 4,4'-isopropylidenedicyclohexanol, iso ... These include sorbide, isomannide, and 3,9-bis(1,1-dimethyl-2-hydroxyethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane (spiroglycol), [8-(hydroxymethyl)-3-tricyclo[5.2.1.02,6]decanyl]methanol, 1,1'-isopropylidine-bis[(p-phenyleneoxy)-2-ethanol], dimer acid diol, hydroquinone bis(2-hydroxyethyl) ether, and resorcinol bis(2-hydroxyethyl) ether.

[0079]

[0081] In some embodiments, the reaction mixture includes 1,3-propanediol, 2-ethyl-2[6,8,8-trimethyl-6-[(trimethylsilyl)oxy]-2,7-dioxa-6,8-disilanona-1-yl] (Silmer OHT A0). In some embodiments, the reaction mixture includes 0.5-5, 1-10, 2-20 mole percent of Silmer OHT A0.

[0080]

[0082] In some embodiments, the reaction mixture includes a small amount of additional diol. In some embodiments, the reaction mixture includes a cyclic ether diol.

[0081]

[0083] In some embodiments, the reaction mixture includes an aromatic diol, such as 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane (HEPP), hydroxyethylresorcinol (HER), or a combination thereof.

[0082]

[0084] In some embodiments, the reaction mixture includes a polyamine.

[0083]

[0085] In some embodiments, the reaction mixture includes a polyol having a molecular weight of 500 to 5,000.

[0084]

[0086] In some embodiments, the polyol component of the reaction mixture comprises a triol or a tetraol.

[0085]

[0087] In some embodiments, the reaction mixture includes a polyether polyol.

[0086]

[0088] In some embodiments, the reaction mixture includes a polyester polyol.

[0087]

[0089] In some embodiments, the reaction mixture includes a polysiloxane polyol.

[0088]

[0090] In some embodiments, the reaction mixture includes a polybutadiene (PBD) based polyol.

[0089]

[0091] In some embodiments, the reaction mixture includes a multifunctional polyol having an average of more than two hydroxyl groups.

[0090]

[0092] In addition to these described polyols, the reaction may include small amounts (<5%) of relatively small polyhydroxy compounds, such as aliphatic or short chain glycols having 2 to 20, 2 to 12, or 2 to 10 carbon atoms. Examples include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol (BDO), 1,6-hexanediol (HDO), 1,3-butanediol, 1,5-pentanediol, neopentyl glycol, hexamethylenediol, heptanediol, nonanediol, dodecanediol, and mixtures thereof.

[0091]

[0093] In some embodiments, the reaction mixture comprises multifunctional branched molecules having greater than two reactive groups per molecule selected from isocyanate, hydroxyl, amine, and thiol groups.

[0092]

[0094] Exemplary branching molecules include tris(2-hydroxyethyl)isocyanurate, glycerin, trimethylolpropane, 1,3,5-tris(hydroxymethyl)benzene, pentaerythritol, diethanolamine, triethanolamine, and their ethoxylates or propoxylates. Additional branching agents include trifunctional or higher functional isocyanates, including polyisocyanates such as hexane diisocyanate or trimers of MDI or IPDI.

[0093]

[0095] In some embodiments, the average functionality of the isocyanate, diol, and polyol combined is greater than 2.0, 2.01, 2.02, 0.03, 2.04, 2.05.

[0094]

[0096] In some embodiments, the reaction mixture includes an additive or catalyst. Examples of urethane catalysts include tertiary amines such as 1,4-diazabicyclo[2.2.2.]octane (DABCO), N-methylmorpholine, N-ethylmorpholine, and the like, tin compounds such as tin(II) laurate, dibutyltin dilaurate, tin mercaptides, bismuth carboxylates, and iron III compounds, and combinations thereof.

[0095]

[0097] In some embodiments, the reaction mixture may include one or more of UV stabilizers, UV absorbers, antioxidant stabilizers (e.g., phenolic, phosphite, thioester, and / or amine, light stabilizers, heat stabilizers, waxes, lubricants, pigments, and dyes.

[0096]

[0098] All of the additives described herein may be used in the reaction mixture in effective amounts known to those of skill in the art for the use of each respective material.

[0097]

[0099] In some embodiments, the TPU compositions described herein may also be blended with one or more other polymers.

[0098]

[0100] In some embodiments, the reaction mixture contains less than 10 mole percent aliphatic diols having less than 9, 8, 7, 6, 5, 4, or 3 carbon atoms.

[0099]

[0101] In some embodiments, the reaction mixture comprises less than 20%, 10%, 5%, 2.5% w / w polymeric diol.

[0100]

[0102] In some embodiments, the diisocyanate component of the reaction mixture comprises greater than 50%, 60%, 70%, 80%, 85%, or 88% MDI.

[0101]

[0103] In some embodiments, the diisocyanate component of the reaction mixture comprises greater than 50%, 60%, 70%, 80%, 85%, or 88% H12MDI.

[0102]

[0104] In some embodiments, the reaction mixture includes a polymeric diol having a glass transition temperature less than 0°C.

[0103]

[0105] In some embodiments, the reaction mixture includes a polypropylene oxide based diol, triol, or tetraol.

[0104]

[0106] In some embodiments, the reaction mixture comprises a polymeric diol having a molecular weight greater than 500.

[0105]

[0107] In some embodiments, the TPU composition comprises a polyisocyanate component selected from 2,4'MDI, 4,4'MDI, a blend of 2,4'MDI and 4,4'MDI, a modified MDI, 2,4'H12MDI, 4,4'H12MDI, a blend of 2,4'H12MDI and 4,4'H12MDI, or a modified H12MDI, one or more linear aliphatic diols, HO-(CH2) x -OH [wherein x=8 to 18, for example, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, or 18], aromatic diols, 1,2-benzenedimethanol, 1,3-benzenedimethanol, 1,4-benzenedimethanol, 1,4-bis(2-hydroxyisopropyl)benzene, 1,4-bis(2-hydroxyethyl)benzene, 2,2'-(o-phenylenedioxy)diethanol, resorcinol bis(2-hydroxyethyl)ether, hydroquinone bis(2-hydroxyethyl)ether, and bis(2-hydroxyethyl)terephthalate, and cyclohexanediols. and a cyclic diol component selected from one or more of cyclohexanedimethanol, cyclohexanediol, isosorbide, isomannide, 4,4'-isopropylidenedicyclohexanol, tetramethylcyclobutanediol, tricyclodecane dimethanol, and spiroglycol, the molar ratio of isocyanate groups to alcohol (NCO ratio) is about 0.95-1.05, 0.97-1.03, 0.98-1.02, and the combined functionality of the isocyanate and alcohol is 1.0-1.005, 1.005-1.02, or 1.01-1.05.

[0106]

[0108] In some embodiments, the diol component of the polyurethane is composed of greater than 80 mole percent cyclohexanedimethanol, 4,4'-isopropylidenedicyclohexanol, bis(2-hydroxyethyl) terephthalate, and linear or branched diols having 9 or more carbon atoms, and has a Tg greater than 95°C, 100°C, 110°C, 115°C, 120°C, or 125°C, and a water absorption less than 2%, 1.75%, 1.5%, 1.25%, or less than 1%.

[0107]

[0109] In some embodiments, the TPU composition has a 24 hour shape recovery of greater than 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or greater than 90%.

[0108]

[0110] In some embodiments, the TPU composition has a 24 hour force retention of greater than 500 grams (g), 600 g, 700 g, 750 g, 800 g, 900 g, 1,000 g, 1,100 g, 1,200 g, 1,300 g, 1,400 g, 1,500 g, 1,600 g, 1,700 g, 1800 g, or greater than 1,800 g.

[0109]

[0111] In some embodiments, the TPU composition has a mustard color dB value of less than 20, 10, 5, or less than 3.

[0110]

[0112] In some embodiments, the TPU composition has an initial color in dB of less than 3, or less than 2, or less than 1.

[0111]

[0113] In some embodiments, the TPU composition has a water absorption after 48 hours at 60° C. of less than 2.20%, 2.10%, 2.00%, 1.90%, 1.80%, 1.75%, 1.70%, 1.65%, 1.60%, 1.55%, 1.50%, 1.45%, 1.40%, 1.35%, 1.30%, 1.25%, 1.20%, 1.15%, 1.10%, 1.05%, or less than 1.00%.

[0112]

[0114] In some embodiments, the TPU composition is substantially amorphous and has a single glass transition temperature of greater than about 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C., 120° C., 125° C., or 130° C. as measured by DSC at 10° C. per minute.

[0113]

[0115] In some embodiments, the TPU composition has a melting point of less than about 240° C., less than 220° C., less than 200° C., or less than about 180° C., as measured by DSC at 10° C. per minute.

[0114]

[0116] In some embodiments, the TPU composition has an elongation at break of greater than 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 100%.

[0115]

[0117] In some embodiments, the TPU composition has an elongation at yield greater than 5%, 6%, 7%, 8%, 9%, or greater than 9%.

[0116]

[0118] In some embodiments, the TPU composition has a flexural modulus of less than 2,500 MPa, e.g., from 350 MPa to 2,500 MPa PSI, from 500 MPa to 2,000 MPa, from 700 MPa to 2,000 MPa, from 1,000 MPa to 1,700 MPa, or from 1,000 MPa to 1,500 MPa.

[0117]

[0119] In some embodiments, the TPU composition has an elastic modulus or tensile modulus of less than 2,500 MPa, from 350 MPa to 2,500 MPa, from 500 MPa to 2,000 MPa, from 700 MPa to 2,000 MPa, from 1,000 MPa to 1,700 MPa, or from 1,000 MPa to 1,500 MPa.

[0118]

[0120] In some embodiments, the TPU composition has a tensile strength of from 5,000 to 15,000 psi.

[0119]

[0121] In some embodiments, the TPU composition has a haze value of less than about 20, 18, 16, 14, 12, 10, 8, 6, 4, or less than about 2 when tested using ASTM D1003.

[0120]

[0122] In some embodiments, the TPU composition has a Shore hardness of from 80A to 85D.

[0121]

[0123] In some embodiments, the TPU composition has a stress crack resistance of greater than 3.5 or greater than 4.

[0122] (Preparation of Thermoplastic Polyurethane (TPU) Composition)

[0124] The TPU compositions may be prepared in one step (batch process), for example by extrusion or casting, or by stepwise or sequential addition of the isocyanate, diol, and other ingredients. The reaction may be accelerated with catalysts and known stabilizers, and processing aids may be incorporated to improve stability or subsequent processing properties.

[0123] (Materials and Methods - Materials)

[0125] Isoplast 2530 amorphous polyurethane, Lubrizol Corporation.

[0124]

[0126] Tritan MP100 Polyester, Eastman Chemical.

[0125]

[0127] Eastar 6763 Polyester, Eastman Chemical.

[0126]

[0128] Aliphatic and cycloaliphatic diols were obtained from Aldrich Chemical or other commercial sources.

[0127]

[0129] Polyisocyanates were obtained from Aldrich Chemical. MDI was ≥98% pure and was purified to remove dimers prior to use. H12MDI was ≥90% pure without further purification.

[0128]

[0130] The dimer aliphatic diol is a C36 diol available from Croda, Inc., New Castle, Del. under the tradename PRIPOL 2033.

[0129] (Materials and Methods - Methods)

[0131] Abrasion resistance is evaluated according to ASTM D4016-19-A using 110 mm circular discs. Samples of 0.030" thickness are pre-weighed to 0.1 mg and abrasion tested using a Nextgen Taber Abrasion Machine with an abrasion wheel CS-17 at 70 rpm for 1000 cycles with a total load of 1000 g. Abrasion is reported as weight loss in mg.

[0130]

[0132] Dynamic Mechanical Analysis (DMA) testing is performed on equipment capable of applying cyclic stress or strain to a material and measuring its response to specific conditions. Various ASTM methods have been established to standardize testing procedures.

[0131]

[0133] Elastic modulus (Young's modulus and tensile modulus), typically reported as megapascals (MPa), is evaluated according to ASTM D638. Unless otherwise specified, samples were tested using a Type IV tensile bar and a speed of 1.27 cm / min.

[0132]

[0134] Elongation at break was evaluated according to ASTM D638, and samples were tested using a Type IV tensile bar and a speed of 1.27 cm / min unless otherwise specified.

[0133]

[0135] The elongation at yield was evaluated according to ASTM D638, and samples were tested using a Type IV tensile bar and a speed of 1.27 cm / min unless otherwise specified.

[0134]

[0136] Flexural modulus is evaluated according to ASTM D790.

[0135]

[0137] Force retention (also called stress retention), e.g., 5%, is measured after a specified period of time on a 0.030" thick, 1.0" wide, 2.0" long specimen using a three-point flexural bending test (with a support span of 0.60"). Either the force at a given time (e.g., 24 hours) or the percentage of the initial force may be reported. Unless otherwise specified, testing is performed in water at a temperature of 37° C. at 5% strain.

[0136]

[0138] Glass transition temperatures and melting points were determined by differential scanning calorimetry (DSC) using a TA Instruments DSC at a heating rate of 10° C. per minute and are reported for the second heating cycle.

[0137]

[0139] Haze / clarity is evaluated according to ASTM D1003-13. 0.030” thick samples polished on both sides by pressing against an optical quality oriented PET film are measured using a transmission haze meter (BYK Haze Guard).

[0138]

[0140] Resistance to stress cracking is measured after rolling into a tube in mouthrinse by microscopic inspection and visual grading for microcracks, with "5" meaning no cracks and "1" meaning extensive cracking and erosion.

[0139]

[0141] Shape recovery is determined using a polymer strip with dimensions of 101.75 x 25.4 x 0.76 mm (length, width, thickness), wrapping the polymer strip around a PVC pipe / tube (diameter 48.25 mm), clamping the two ends, and immersing for 24 hours in deionized (DI) water at 37°C or mouthwash at 25°C. Recovery is measured at T=0 and 24 hours after wrapping into a tube. The diameter of the tube is selected to impart a 5% strain. At the end of the test period, the clamps are removed and the strip is allowed to recover freely in air for 24 hours. The 24 hour shape recovery (%) is calculated according to the following formula: 24 hour shape recovery (%)=100×(1-(((L-L24) / (L-L0))), [In the formula, L = total length of strip, 101.75mm L0 = distance between the ends of the clamped strip, 43.5 mm L24 = distance between the ends of the free strip after 24 hours of recovery (mm)] is determined in accordance with

[0140]

[0142] Shore hardness is assessed according to ASTM D2240 using a durometer that measures the penetration of a metal foot or pin into the surface of a material, unless otherwise specified.

[0141]

[0143] Stain resistance (reported as stain dB value) is the change in dB value (using the CIE LAB color scale) of a 0.76 mm thick film sample after 24 hours exposure to mustard. Stain dB value is determined with color evaluated on a white tile using a colorimeter before and after exposure to mustard. Unless otherwise stated, samples are immersed in French's Classis Yellow Mustard (French's Food Company, LLC) for 24 hours at 37°C. The color of the sample is measured before (as initial color in dB) and after (as final color in dB) the staining process. Colored dB value = final color in dB - initial color in dB

[0142]

[0144] Tensile strength (the maximum stress a material can handle) is evaluated according to ASTM D638. Unless otherwise specified, samples were tested using a Type IV tensile bar and a speed of 1.27 cm / min.

[0143]

[0145] Thermoforming open time is evaluated using 125 mm x 0.030" thick sheets (dried to a moisture level of less than 0.05% w / w) placed on a wire rack at 20°C and 50% relative humidity (RH). After various time periods, the samples are placed in an IR thermoformer and rapidly heated to 200°C for 60 seconds or until 1 inch sag. Samples are considered to have failed if there are more than 5 bubbles larger than 0.5 mm. Results are reported as time to fail or pass / fail after a specific time period.

[0144]

[0146] Water absorption is evaluated using polymer samples with a thickness of 0.76 mm + / - 0.1 mm, which are first dried in a vacuum oven at 100°C for at least 8 hours, then placed in 60°C water for 48 hours, removed from the water, wiped dry and the weight gain of the sample is measured. Equilibrium moisture absorption = 100 x [(weight final - weight initial) / weight initial]. Preparation of polyurethane.

[0145]

[0147] Batch process. The diol and additives are weighed into a vessel and optionally heated until melted. The polyisocyanate is added to the vessel all at once or in stages. Catalyst is added to the vessel, if necessary. The vessel is placed in a centrifugal mixer and mixed for 3 minutes or more until the entire volume solidifies. The vessel is then heated to a temperature of 120° C. for 12 hours to complete the reaction.

[0146]

[0148] The cured specimens were removed from the container, pressed at 400°F to 450°F to a thickness of approximately 2 mm, and then compression molded to a thickness of approximately 0.76 mm. The pressed specimens were conditioned at ambient conditions for 24 hours before testing.

[0147]

[0149] Stepwise process. The polymer microstructure can be easily adjusted by modifying the reaction process. The polyol may be first reacted with an excess of polyisocyanate to produce isocyanate-terminated oligomers, and then mixed with the diol and additional polyisocyanate. Alternatively, the first diol component is mixed and reacted with a portion of the total isocyanate, followed by the addition of the second diol component and optionally additional isocyanate to produce a block-like microstructure.

[0148]

[0150] The present disclosure is further illustrated by the following examples, which are provided for illustrative purposes only and should not be construed as limiting the scope or content of the present disclosure in any way. EXAMPLES

[0149] (Example 1. Commercially available polyurethane material.)

[0151] Comparative Example 1 (CE1) Isoplast 2530 (Lubrizol) was extruded into a 0.030" thick sheet. Isoplast 2530 is composed of hexanediol and 4,4'-MDI and has a Tg of 81-89°C (Table 2 of Isoplast Processing Guide; Lubrizol).

[0150]

[0152] CE2: Isoplast 2531 (Lubrizol) was formed into a 0.030" thick sheet. Isoplast 2531 is composed of hexanediol, cyclohexanedimethanol, polytetramethylene oxide diol, and 4,4'-MDI with a Tg of approximately 101-109°C (Table 2 in Isoplast Processing Guide; Lubrizol).

[0151]

[0153] CE3: The Ex1 material of the present invention was prepared by reacting 2000 MW polycaprolactone diol with 1,9-nonadiol and 4,4'-MDI according to the procedure of US Patent Application Publication No. 2018 / 0127535A1 to prepare a polymer having approximately 34% soft blocks and 66% hard blocks.

[0152]

[0154] CE4: The procedure provided in Example 1 of WO 2020 / 225651 was used. A polymer composed of MDI, hexanediol, and 37% fatty acid-based dimer alcohol diol was prepared.

[0153] (An experimental polyurethane material.)

[0155] Preparation of polyurethane.

[0154]

[0156] Additional polyurethanes listed in Table 1 were prepared by a batch process and compression molded into plaques for evaluation.

[0155]

[0157] [Table 1]

[0156]

[0158] The relationship between equilibrium water absorption and shape recovery is further illustrated in FIG.

[0157]

[0159] As can be seen, lower equilibrium water absorption correlates with improved shape recovery. Materials with long chain diols (C10 and C12) perform better than C6, with C12 partially replacing C6 resulting in higher equilibrium water absorption and poorer shape recovery. Samples were also evaluated for force retention (5% strain, 3-point bend, in water at 37° C.) and the results are shown in Table 2.

[0158]

[0160] [Table 2]

[0159]

[0161] Experimental samples 1 and 6 containing hexanediol have higher equilibrium water absorption and lower force retention despite having high initial modulus values. EXPs 2, 3, 4 and 5 were composed of dodecanediol and cyclic diols, respectively, which increased the glass transition and improved stress retention. Even the addition of 25 mol percent of the more hydrophilic hexanediol reduced the retained force from 1,600 grams to 1,138 grams.

[0160]

[0162] Additional tests were performed to examine the effect of the compositions on glass transition temperature, shape recovery, stress retention, color, and other properties of interest.

[0161]

[0163] [Table 3]

[0162]

[0164] [Table 4]

[0163]

[0165] These tests show that polyurethane compositions made of MDI and 1,6-hexanediol have poor stress retention, which is believed to be due, at least in part, to high equilibrium water absorption. Prior art example CE3, which contains a longer chain diol (C9) and a soft block of polyester, has very poor shape recovery and extremely low stress retention. This may be due to the low glass transition temperature and low modulus of elasticity of the polyester. Similarly, prior art example CE4, which contains a hard block of hexanediol and a soft block of dimer acid-based diol, has poor shape recovery, stress retention, and is also significantly colored.

[0164]

[0166] EX7, consisting only of dodecanediol and MDI, has a low Tg, poor shape recovery, and low stress retention.

[0165]

[0167] EX8, composed only of CHDM and MDI, has a higher than desired modulus and Tg, and has very low elongation at break, making it an unusable material for use in manufacturing dental appliances. The EX9, 10, 11, 12, 13, and 14 materials are composed of long chain diols and cyclic diols, which increase the Tg and provide a surprising combination of excellent shape recovery, stress retention, and low color.

[0166]

[0168] Of particular note, samples EX8, 9, 11, and 12, utilizing a combination of long chain diol and cyclohexanedimethanol, have yield elongation values ​​greater than 6% and as high as 8%, which is unexpected and highly desirable. The reason for this high value is unclear. Additionally, sample EX14, consisting of dodecanediol and isosorbide, has a measured yield elongation of 7.4%, which is very high for a stiff polyurethane. On the other hand, surprisingly, samples CE3, CE4, and EX15, which contain soft domains, either do not show a clear yield point or show a low yield point.

[0167]

[0169] Figure 2 shows the relationship between glass transition temperature and shape recovery for these materials. Materials disclosed herein with Tg values ​​above 100C perform better than materials with lower values.

[0168]

[0170] [Table 5]

[0169]

[0171] The introduction of a flexible polyol such as PTHF can help improve the elongation at break to over 100%. This is accompanied by an increase in color dB values, as shown in EX17 and 18. Of particular interest, the TPU with bis(2-hydroxyethyl) terephthalate has a high elongation at break percentage with a very low color dB value, as shown in EX20 and 21.

[0170]

[0172] [Table 6]

[0171]

[0173] Further modification of properties can be achieved by replacing MDI with H12MDI as the diisocyanate monomer, providing a slightly "softer" TPU. As shown in the above table, EX22-25 provide a low modulus, much improved elongation at yield, elastic recovery, and force retention, while the color dB values ​​are slightly higher. In particular, EX22 has an elongation at yield measured at 9.5%; EX23 and 24 have a 24 hour shape recovery measured at over 85%; and EX25 has a 24 hour force retention measured at over 1880g. On the other hand, the introduction of the more flexible H12MDI monomer also provides the TPU material with advantages regarding high temperature processing in less yellowing and higher flowability.

[0172]

[0174] Preparation of TPU with block-like structure. A polyurethane was prepared with a final molar composition ratio of 1.02 MDI, 0.45 C12 diol, and 0.55 CHDM. Dodecanediol (45 mol%) and CHDM (10 mol%) were mixed and melted, then 102 mol% MDI was added, the reaction was allowed to proceed with mixing, followed by 45 mol% CHDM.

[0173]

[0175] Branched Polyurethanes Polyurethanes were prepared and characterized as shown in Table 3e.

[0174]

[0176] [Table 7]

[0175]

[0177] These examples show that very little multifunctional monomer can significantly affect the elastic modulus, increasing shape recovery and force retention without impairing thermoplastic processing. The material of Example 31 has nearly 50% greater force retention at 24 hours than Example 29.

[0176]

[0178] [Table 8]

[0177]

[0179] Table 3f shows examples of several H12MDI-based TPUs prepared with very little trifunctional monomer acting as a crosslinker. These materials have excellent chemical resistance under stress and to various media such as mouthwash, with a rating of 5 compared to a rating of 3 for EX23, which does not have a trifunctional monomer.

[0178]

[0180] The EX13 material is used as the A layer in an ABA 3-ply sheet, and the B layer is a Shore 50D aromatic polyether polyurethane that has excellent interlayer adhesion, high tear strength, and excellent stress retention.

[0179]

[0181] When the sheet materials of EX7-EX15 are thermoformed over a dental model, they can be used to manufacture appliances for positioning teeth.

[0180]

[0182] Small amounts of polyols, particularly polytetramethylene glycols having MW between 650 and 5,000, have been incorporated to produce phase separated polymers (as determined by DSC), improve impact resistance, lower modulus, and increase tear strength. Preferably, the amount is less than about 7.5, 5, or 2.5 weight percent.

[0181]

[0183] Although specific embodiments of the present disclosure have been described, various modifications, combinations, variations, alternative structures, and equivalents are also included within the scope of the present disclosure. The embodiments of the present disclosure are not limited to a specific method for producing a TPU composition, but may employ any method for producing a TPU composition known to those skilled in the art. Additionally, although the embodiments of the present disclosure have been described using a specific sequence of processes and steps, it should be clear to those skilled in the art that the scope of the present disclosure is not limited to the sequence of processes and steps described.

[0182]

[0184] Accordingly, the specification and drawings are to be regarded in an illustrative rather than a restrictive sense, but it will be apparent that additions, subtractions, deletions and other modifications and changes may be made thereto without departing from the broader spirit and scope.

Claims

1. 1. A thermoplastic polyurethane (TPU) reaction mixture comprising a diol component and a diisocyanate component, The diol component is represented by the general formula HO-(CH 2 ) x at least one linear aliphatic diol having -OH, where x is an integer from 9 to 18, and one or more cyclic diols or one or more aromatic diols having 6 or more carbons, the molar ratio of isocyanate groups to alcohol (NCO ratio) being about 0.95 to 1.05, said reaction mixture comprising less than 20% of a polymeric diol component having a glass transition temperature of less than 0°C; TPU reaction mixture.

2. 2. The TPU reaction mixture of claim 1, wherein the diisocyanate component comprises one or more of MDI, TDI, PDI, HDI, H12MDI, IPDI, XDI, CHDI, or HXDI.

3. 3. The TPU reaction mixture of claim 2, wherein the diisocyanate component comprises greater than 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 88% MDI.

4. 3. The TPU reaction mixture of claim 2, wherein the diisocyanate component comprises greater than 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 88% H12MDI.

5. 2. The TPU reaction mixture of claim 1, wherein the diol component comprises greater than 80 mole percent cyclohexanedimethanol, 4,4'-isopropylidenedicyclohexanol, bis(2-hydroxyethyl) terephthalate, and a linear or branched diol having 9 or more carbon atoms.

6. 2. The TPU reaction mixture of claim 1, wherein the aliphatic diol component comprises one or more of 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, and 1,18-octadecanediol.

7. 2. The TPU reaction mixture of claim 1, wherein the cyclic diol component comprises one or more of cyclohexanedimethanol, tetramethylcyclobutanediol, hydrogenated bisphenol A, cyclohexanediol, and isosorbide.

8. 2. The TPU reaction mixture of claim 1, wherein the aromatic diol component comprises one or more of 1,2-benzenedimethanol, 1,3-benzenedimethanol, 1,4-benzenedimethanol, 1,4-bis(2-hydroxyisopropyl)benzene, 1,4-bis(2-hydroxyethyl)benzene, 2,2'-(o-phenylenedioxy)diethanol, resorcinol bis(2-hydroxyethyl)ether, hydroquinone bis(2-hydroxyethyl)ether, and bis(2-hydroxyethyl)terephthalate.

9. 9. The TPU reaction mixture of any one of claims 1 to 8, comprising multifunctional branched molecules having greater than two reactive groups per molecule selected from isocyanate, hydroxyl, amine, and thiol groups.

10. 9. The TPU reaction mixture of any one of claims 1 to 8, comprising additives or catalysts such as tertiary amines, tin compounds, bismuth compounds, and iron III compounds, and combinations thereof.

11. 9. The TPU reaction mixture of any one of claims 1 to 8, comprising one or more of UV stabilizers, UV absorbers, antioxidant stabilizers (such as phenolic, phosphite, thioester, and / or amine), light stabilizers, heat stabilizers, waxes, lubricants, pigments, and dyes.

12. A TPU composition prepared using the reaction mixture of any one of claims 1 to 8, wherein the polymer is blended with one or more other polymers.

13. A TPU composition prepared using the reaction mixture of any one of claims 1 to 8, wherein the polymer is substantially amorphous and has a glass transition temperature above 85°C and below 150°C.

14. A TPU polyurethane composition prepared using the reaction mixture of any one of claims 1 to 8, wherein the polymer is substantially amorphous and has a viscosity of 100°C or 110°C or more and 150°C or more. o C.

15. A TPU composition prepared with the reaction mixture of any one of claims 1 to 8, having a Stress Retention of more than 500 grams or more than 750 grams and less than 2500 grams or less than 3000 grams.

16. A TPU composition prepared using the reaction mixture of any one of claims 1 to 8, having a water absorption of less than 1.80% or less than 2.20% and more than 0.40% after 48 hours at 60°C.

17. A TPU composition prepared with the reaction mixture according to any one of claims 1 to 8, having an elongation at yield greater than 6% and less than 12%.

18. A TPU composition prepared with the reaction mixture according to any one of claims 1 to 8, having an elongation at yield of more than 7% and less than 12%.

19. A TPU composition prepared with the reaction mixture according to any one of claims 1 to 8, having an elongation at yield of more than 8% and less than 12%.

20. 9. A TPU composition prepared with the reaction mixture of any one of claims 1 to 8, having an elongation at break of more than 55%, or more than 75%, or more than 95%, and less than 200%.

21. A TPU composition prepared using the reaction mixture of any one of claims 1 to 8, the TPU composition having a dB color value of less than 10, or less than 3.

22. A TPU composition prepared using the reaction mixture of any one of claims 1 to 8, the TPU composition having an initial color in dB of less than 3, or less than 2, or less than 1.

23. A TPU composition prepared using the reaction mixture of any one of claims 1 to 8, having a flexural modulus of 500 MPa to 2,500 MPa.

24. A TPU composition prepared using the reaction mixture of any one of claims 1 to 8, having an elastic or tensile modulus of 500 Mpa to 2,500 Mpa.

25. A TPU composition prepared using the reaction mixture of any one of claims 1 to 8, the TPU composition having a haze value of less than 10, or less than 6.

26. 9. A TPU composition prepared with the reaction mixture of any one of claims 1 to 8, which when thermoformed exhibits a force retention of greater than 800 g when a 0.76 mm thick sample is tested at 5% strain for 24 hours at 37°C.

27. 9. A TPU composition prepared using the reaction mixture of any one of claims 1 to 8, which exhibits a higher Tg and substantially no increase in water absorption compared to a thermoplastic polyurethane composition comprising an aliphatic diol and lacking a cyclic diol.

28. A polymer sheet composition comprising the TPU composition of claim 13.

29. 14. A multi-layer TPU laminate comprising the TPU composition of claim 13.

30. 30. A dental appliance capable of reversible deformation conforming to one or more teeth comprising the polymer sheet composition of claim 28.

31. 30. A dental appliance capable of reversible deformation conformal to one or more teeth comprising the multi-layer TPU laminate of claim 29.